The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1080/13811118.2010.494133
|View full text |Cite
|
Sign up to set email alerts
|

Bullying, Cyberbullying, and Suicide

Abstract: Empirical studies and some high-profile anecdotal cases have demonstrated a link between suicidal ideation and experiences with bullying victimization or offending. The current study examines the extent to which a nontraditional form of peer aggression--cyberbullying--is also related to suicidal ideation among adolescents. In 2007, a random sample of 1,963 middle-schoolers from one of the largest school districts in the United States completed a survey of Internet use and experiences. Youth who experienced tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

55
870
9
83

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,593 publications
(1,117 citation statements)
references
References 41 publications
55
870
9
83
Order By: Relevance
“…Yapılan araştırmaların bir kısmı (Hinduja ve Patchin, 2010;Slonje ve Smith, 2008;Wolak, Mitchell ve Finkelhor, 2002) bu araştırmayla tutarlı biçimde kızların erkeklerden daha çok siber zorbalık yaptığını ortaya koymaktadır. Bununla birlikte erkeklerin kızlardan daha çok siber zorbalık yaptığını (Arıcak ve diğerleri, 2008;Dilmaç, 2009;Vanbosch ve VanCleemput, 2009;Williams ve Guerra, 2007) bildiren araştırmalar da bulunmaktadır.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
See 1 more Smart Citation
“…Yapılan araştırmaların bir kısmı (Hinduja ve Patchin, 2010;Slonje ve Smith, 2008;Wolak, Mitchell ve Finkelhor, 2002) bu araştırmayla tutarlı biçimde kızların erkeklerden daha çok siber zorbalık yaptığını ortaya koymaktadır. Bununla birlikte erkeklerin kızlardan daha çok siber zorbalık yaptığını (Arıcak ve diğerleri, 2008;Dilmaç, 2009;Vanbosch ve VanCleemput, 2009;Williams ve Guerra, 2007) bildiren araştırmalar da bulunmaktadır.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Yapılan araştırmalar siber zorbalık ve mağduriyet ile cinsiyet, yaş (Ayas ve Horzum, 2012;Hinduja ve Patchin, 2010;Peker ve Eroğlu, 2013;Peker, Eroğlu ve Çitemel, 2012), ailenin aylık geliri (Arslan, Savaşer, Hallett ve Balcı, 2012), anne ve babanın eğitim düzeyi, anne ve babanın birlikte yaşama durumu (Mitchell, Finkelhor ve Wolak, 2003), internete bağlanılan yer (Akbulut, Şahin ve Erişti, 2010), internet kafeye gitme sıklığı (Akbulut ve Erişti, 2011), internetin aşırı kullanımı , bilgisayar kullanma becerisi (Ybarra ve Mitchell, 2004), ergenin anne ve babasının bilgisayar becerisine ilişkin algısı, interneti kullanma amaçları (Akbulut ve diğerleri, 2010), ebeveyn ve okul personelinin denetimi (Kabalcıoğlu ve Eroğlu, 2013;Spears, Slee, Owens ve Johnson, 2008), filtre programı kullanma (Eroğlu, 2014;Mitchell, Finkelhor ve Wolak, 2005) ve sosyal paylaşım sitelerini kullanma sıklığı (O'Dea ve Campbell, 2012) arasında anlamlı ilişkiler bulunduğunu rapor etmişlerdir.…”
unclassified
“…[4][5][6][7][8][9][10] In other words, we may suppose that RW and VW activities that we studied are the parts of a continuum that our participants behave similarly while they're online or offline. Similar significant correlations were found between RW and VW activities for different age groups.…”
Section: Virtual-world and Real-world Activities 265mentioning
confidence: 99%
“…For example, the research on bullying-cyberbullying and online-offline aggression indicated that these behaviors were correlated to each other. [4][5][6] Moreover, offline victims were found to be online victims. 7,8 Beyond these problematic behaviors, social networks in RW and offline friendships seem to continue in VW.…”
mentioning
confidence: 99%
“…An extensive body of research suggests that suicidal behaviour occurs as the result of a complex interaction between numerous cumulative factors (e.g., Dieserud et al, 2001; O" Connor & Sheehy, 2001;Panagioti, Gooding, Taylor, & Tarrier, 2013;Taylor et al, 2010;Wasserman et al, 2007) Therefore, a biopsychosocial conceptualisation of suicidal behaviour is utilised within many clinical settings (e.g., Hoffman, 2000;King & Merchant, 2008;O"Connor & Nock, 2014;O"Connor & Sheehy, 2000). The influential role of social or interpersonal factors in the development of suicidality (i.e., suicidal thoughts, feelings and behaviours) has been substantially documented within the research literature, in both clinical and non-clinical populations (e.g., Coker et al, 2002;Hawton et al, 2012;Hinduja & Patchin, 2010;Jakupcak et al, 2010). However, the role of such factors within pathways leading to suicidal behaviour is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%